Sprzętowa implementacja rozmytych sieci Petriego jako układów sterowania - Hajduk, Zbigniew
The main goal of the thesis was development of new, effective methodology of the fuzzy Petri net transformation, which may be treated as formal desctription of a control algorithm of some process - into the digital circuit, assembled using FPGA matrix structures, both as synchronous and asynchronous systems. In the work are discussed: fuzzy Petri nets, asynchronous (self clocked) digital sequential circuits and their implementation using Field-Programmable Gate Arrays (FPGA), and the automation of digital systems described by Petri nets, together with their implementation using Verilog hardware description language. The following problems were solved:
Keywords: systemy rozmyte; sieci Petriego; informatyka; systemy cyfrowe